Business-Level Strategy Transformation, Competitive Rivalry, and Competitive Dynamics: A Bibliometric Study of Digitalization Trends and Global Competition - Arenal Arenal; Rendy Ardiansyah; Suparno Suparno; Saparuddin Saparuddin (Journal of Social Research, 2025)
This study examines the evolution of Business-Level Strategy, Competitive Rivalry, and Competitive Dynamics through a bibliometric analysis of 658 articles from the Scopus database spanning the years 2000 to 2024. Its aim is to identify research trends, publication patterns, and the interconnections among various business strategy concepts. The findings from the keyword co-occurrence analysis indicate that digitalization and innovative technology are at the forefront of contemporary business strategies. Furthermore, Competitive Rivalry is increasingly centered on both offensive and defensive strategies, as well as the concept of coopetition. In the realm of Competitive Dynamics, it is evident that sustainability, digital transformation, and compliance with global regulations are critical factors shaping strategic decision-making within organizations. As uncertainty in the industry continues to rise, companies must develop strategies that harness big data analytics, artificial intelligence, and digital business platforms to maintain their competitive edge on a global scale. This study enriches academic literature by mapping the evolution of business strategies and offers valuable insights for companies seeking to design adaptive strategies in response to technological changes and market dynamics.